Evaluation of gamma and electron radiations impact on vitamins for onion preservation. (January 2021) - Firouzi, Salar; Khorshidi, Abdollah; Soltani-Nabipour, Jamshid; Zia Barzi, Seyed Mohsen; Amani, Mohammad; Ay, Mohammad Reza
Abstract: Food irradiation is a process in which food and other consumer products are exposed to gamma rays, X-rays or electron beams after extraction. This method is particularly important in order to reduce infectious agents and to extend the shelf life of the product. The target radiation is done with different devices, so self-sufficient radiation and panoramic radiation —including product and source overlap, planar and categorical radiation— is the major characteristics. Besides, a high performance liquid chromatography device (10% methanol, 70%–80% distilled water and 10% ethanol) is utilized to measure the chemical substance of pyridoxine (vitamin B3), thiamine (vitamin B6) and vitamin C of Vidalia or sweet onions. In our research, gamma-cell 220 and Rhodorton electron facilities were utilized to irradiate the onion crop. This project focuses on increasing the shelf life of agricultural products, especially onions, using energy of 1.25 MeV for both gamma irradiation and electron beam, and measuring the amount of vitamins B3, B6 and C, which are the nutrients of this product. The prepared onion samples were exposed under electron and gamma irradiations by two doses of 200 and 500 Gy at 25 °C. Then, a liquid chromatography device was utilized to measure the vitamins. The results showed that the onions were not damaged by 200 Gy doses and their nutritional properties were preserved, which means that not only can vitamins with this dose be retained without any spoilage for 30 days, but also eliminate pathogenic microorganisms. The process indicated that using 200 Gy radiations does not endanger the health of food and consumers. Highlights: Onion sustainability via electron and gamma irradiation was investigated by 200 and 500 Gy doses. B3, B6 and C vitamins amounts were measured by using liquid chromatography. 200 Gy dose revealed more sustainability and shelf life extension up to 30 days without any spoil.